2016
DOI: 10.1002/asi.23635
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly publication and collaboration in Brazil: The role of geography

Abstract: Brazilian scholarly output has rapidly increased, accompanied by the expansion of domestic collaborations. In this paper, we identify spatial patterns of collaboration in Brazil and measure the role of geographic proximity in determining the interaction among researchers. Using a database comprising more than one million researchers and seven million publications, we consolidated information on interregional research collaboration in terms of scientific coauthorship networks among 4,615 municipalities during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 48 publications
1
32
0
11
Order By: Relevance
“…For instance, Hoekman, Frenken, and Tijssen () examined the changing spatial patterns of collaboration within Europe and found that geographic distance was still related to collaboration. Similarly, Sidone, Haddad, and Mena‐Chalco () found that, although collaboration showed a trend of geographic deconcentration in Brazil, distance still significantly determined the intensity of knowledge flow in collaboration networks. In terms of geographic barriers, the migration and mobility of scientists could be another way to transcend establishing ties.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 92%
“…For instance, Hoekman, Frenken, and Tijssen () examined the changing spatial patterns of collaboration within Europe and found that geographic distance was still related to collaboration. Similarly, Sidone, Haddad, and Mena‐Chalco () found that, although collaboration showed a trend of geographic deconcentration in Brazil, distance still significantly determined the intensity of knowledge flow in collaboration networks. In terms of geographic barriers, the migration and mobility of scientists could be another way to transcend establishing ties.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 92%
“…A generalization of this result suggests that Rodríguez and Pepe (2008) findings emerges: co-authorship is primarily driven by departmental and institutional affiliation. The role of geography in scientific collaborations is also remarked by the location of each university: academic production tends to focus on regional problems [Guerci Sidone et al (2014) study the role of geography in Brazilian academic production].…”
Section: Co-authorship Networkmentioning
confidence: 99%
“…Collaboration frequently happens to most of the scholars especially in science and engineering subject area in order to stimulate the productivity in publication. [125,126] In science and engineering field, usually there are many members in one team for R&D. [117,118] This opportunity commonly attracts some international scholars to work together in ongoing research. Hence, the collaboration with other countries formed.…”
Section: Collaboration Countriesmentioning
confidence: 99%